2001
DOI: 10.4049/jimmunol.167.7.3980
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Long Chain Polyunsaturated Fatty Acid, β-Oxa 21:3n-3, Inhibits T Lymphocyte Proliferation, Cytokine Production, Delayed-Type Hypersensitivity, and Carrageenan-Induced Paw Reaction and Selectively Targets Intracellular Signals

Abstract: A novel polyunsaturated fatty acid (PUFA), β-oxa 21:3n-3, containing an oxygen atom in the β position, was chemically synthesized, and found to have more selective biological activity than the n-3 PUFA, docosahexaenoic acid (22:6n-3) on cells of the immune system. Although β-oxa 21:3n-3 was very poor compared with 22:6n-3 at stimulating oxygen radical production in neutrophils, it was more effective at inhibiting human T lymphocyte proliferation (IC50 of 1.9 vs 5.2 μM, respectively). β-Oxa 21:3n-3 also inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…␤-oxa, ␤-thia, and ␥-thia PUFA and their methyl esters were synthesized, as described previously (5)(6)(7)(8). All fatty acid stocks (20 mM in chloroform or ethanol) were stored at Ϫ20°C.…”
Section: Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…␤-oxa, ␤-thia, and ␥-thia PUFA and their methyl esters were synthesized, as described previously (5)(6)(7)(8). All fatty acid stocks (20 mM in chloroform or ethanol) were stored at Ϫ20°C.…”
Section: Fatty Acidsmentioning
confidence: 99%
“…Recently, we have demonstrated that one of these, ␤-oxa 21: 3n-3, had similar biological properties as the 15-hydroperoxyeicosatetraenoic acid (15-HPETE), which markedly depressed T cell function and the inflammatory response, but was a poor stimulator of the respiratory burst in neutrophils (7). The availability of a range of novel PUFA with different structural modifications has enabled us to better define the relationship between specific structural elements of these novel fats and their biological properties.…”
mentioning
confidence: 99%
“…pecific lipid-derived mediators can exert opposing actions on T cell proinflammatory functions (1)(2)(3). The key role of the classic eicosanoids, such as the prostanoids in the regulation of inflammatory and autoimmune disorders, is also well appreciated (4).…”
mentioning
confidence: 99%
“…The key role of the classic eicosanoids, such as the prostanoids in the regulation of inflammatory and autoimmune disorders, is also well appreciated (4). In rheumatoid arthritis, which is mediated in part by the activation and recruitment of Ag-specific lymphocytes (5), leukotriene (LT) 3 B 4 generated locally can control T cell activation, regulating the inflammatory response (6,7).…”
mentioning
confidence: 99%
“…29). T cells were then stimulated for 48 h with PHA (2 g/ml; Murex Diagnostics and PMA (10 ng/ml; Sigma-Aldrich)) diluted in RPMI 1640 containing 5% heat-inactivated blood group AB serum (5% ⌬AB serum) at 37°C in 5% CO 2 and high humidity.…”
Section: Lymphoproliferationmentioning
confidence: 99%